Publication and Dating of the Exploration Scientifique de l’Algérie: Histoire Naturelle des Animaux Articulés (1846–1849) by Pierre Hippolyte Lucas - Evenhuis, Neal L. (Zootaxa, 2012)
The history of the Exploration Scientifique de l’Algérie and the publication of its results are given. The contents of theplates and text for the livraisons of the 3-volume set of Pierre Hippolyte Lucas’s Histoire Naturelle des Animaux Articulésare researched and dates of publication proposed, with annotations given on the composition of text and plates of eachlivraison, including notice of the dating of plates of birds, fish, reptiles, and mammals, the new names therein which pre-date their publication in text in some cases as much as 20 years later. An index to all taxa proposed as new in this work is presented giving the earliest known date of publication for each name.